Investigação sobre o rompimento da barragem de rejeitos do fundão, em Mariana/MG, a partir de uma abordagem multidisciplinar - Barbosa, Sidney de Oliveira (2022)
On the afternoon of November 5, 2015, the Fundão tailings disposal dam, owned by the mining company SAMARCO, located in the Germano Mining Complex, municipality of Mariana, State of Minas Gerais, Brazil, collapsed. As a result, a large part of its content, around 60 million cubic meters, consisting of sandy tailings and mud, was dumped into streams downstream of the aforementioned dam and then into the Rio Doce. The disaster caused the loss of 19 (nineteen) human lives, the devastation of the District of Bento Rodrigues, the interruption of water supply in 39 (thirty-nine) municipalities in the States of Minas Gerais and Espírito Santo, and the destruction of goods and properties on its way of more than 650 km, until it reaches the Atlantic Ocean. It is considered the biggest environmental disaster in the history of Brazil. The present work aimed to identify, based on the experience of the concrete case of the Fundão dam failure, the main causes of the disaster, as well as the interactions and relationships between the various actors, technical and natural elements involved in the planning, implementation and operation of this structure type. The Constellation Analysis technique, developed at the Technical University of Berlin in the early 2000s, was applied, designed to study complex situations from a multidisciplinary approach. The application of the aforementioned analysis technique allowed to identify that the factors that would have contributed to the occurrence of the liquefaction phenomenon, pointed out by experts as the immediate cause of the collapse, resulted, directly or indirectly, from actions and/or omissions of various actors involved in the process, which include designers, consultants, those responsible for the construction and operation of the dam, company managers, bodies responsible for environmental licensing and the operating license for mining activity on the site, among others. Existing gaps in legislation and normative instruments were also found, often omitted in relation to important aspects that must be taken into account in the implementation of tailings dams, in a safe way.